2015
DOI: 10.1186/s13705-015-0068-2
|View full text |Cite
|
Sign up to set email alerts
|

A tale of three transitions: a year in the life of electricity system transformation narratives in the Irish media

Abstract: Background: This paper focuses on discourses of transition in the electricity system in the Irish print media, with particular attention to both the framing and the scalar referents of the debate. We characterise some of the key contextual drivers for system transformation and suggest that too sharp a distinction between existing electricity infrastructure and systems of the future forecloses the possibility of social learning. Our central question research question is: What lessons can emergent techno-optimis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…For example, Skjølsvold [ 83 ] in finding that the media presents varying perspectives on bioenergy, suggested that the media may be indeed impacting public perceptions. As well, smart grid media discourse in Irish print media has been found to be problematic by failing to pay attention to crucial issues, such as ownership and scale [ 84 ]. The current paper contributes to this broader emerging literature by highlighting the role media discourse may be having on public perceptions of wind power.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Skjølsvold [ 83 ] in finding that the media presents varying perspectives on bioenergy, suggested that the media may be indeed impacting public perceptions. As well, smart grid media discourse in Irish print media has been found to be problematic by failing to pay attention to crucial issues, such as ownership and scale [ 84 ]. The current paper contributes to this broader emerging literature by highlighting the role media discourse may be having on public perceptions of wind power.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change and environmental degradation pose a threat to Europe and the rest of the world. To meet these challenges, Europe needs a new growth strategy to transform the energy market into a modern, resource-efficient, and competitive economy with the following characteristics [25,26]:…”
Section: Justificationmentioning
confidence: 99%
“…Local communities also contribute to the broader socio-political acceptability of new policy narratives (Mullally and Byrne, 2016). Implementation of a reuse and recycling strategy requires detailed qualitative analysis to understand how communities will respond to a proposed strategy taking into account the geographical, temporal, socio-political and cultural context (Aitken, 2010).…”
Section: Frp Windmentioning
confidence: 99%